HCG Trigger After Failed GnRH Agonist Trigger Resulted in Two Consecutive Live Births: A Case Report - Liest, Sara; Riishede Christiansen, Iben; Prætorius, Lisbeth; Bogstad, Jeanette; Freiesleben, Nina la Cour; Pinborg, Anja; Løssl, Kristine (Frontiers in Reproductive Health, 2021)
Abstract: Background: Failed GnRH agonist trigger with no oocyte retrieved during aspiration of several follicles is a rare but recurrent situation that can be rescued by termination of the aspiration procedure, re-triggering by human chorion gonadotropin (hCG) and repeated oocyte pickup 36 hours later. Failed GnRH agonist trigger is frustrating and unsatisfactory and fertility doctors must be aware of possible hCG re-triggering and retained opportunity for successful cycle outcome. Objective: In this case report we present a woman who experienced failed GnRH agonist trigger and rescue hCG re-trigger followed by two consecutive live births after frozen-thawed single blastocyst transfers. Methods: A Case report. Results: Two healthy children were born in 2018 and 2020 respectively as a result of controlled ovarian stimulation for IVF, failed GnRH agonist trigger followed by hCG re-trigger and successful retrieval of 25 oocytes. Conclusion: Re-triggering with hCG after failed GnRH agonist trigger can result in consecutive live births and such knowledge can prevent cycle cancellation and patient discouragement. Knowledge on re-triggering with hCH and consecutive live births after failed GnRH agonist trigger can prevent cycle cancellation and patient discouragement.